A Survey on Optimal Control and Operation of Integrated Energy Systems. (25th December 2019) - Wei, Chun; Xu, Xiangzhi; Zhang, Youbing; Li, Xiangshan
Abstract : At present, the transformation of energy structure is at a critical stage, and emerging renewable energy technologies and multienergy equipment have been widely used. How to improve the energy efficiency of integrated energy system (IES) and promote large-scale absorption of renewable energy is of great significance to the application forms of energy in the future. The development of new internet technology and sensor technology provides strong technical support for the optimal operation and coordinated control of IES. In recent years, the IES is experiencing unprecedented changes, which has attracted great attention from academia and industry. In this paper, the optimal control and operation behavior of IES are reviewed. Firstly, the research status of IES in recent years is summarized. Then, the modeling methods of different equipment in IES are analyzed in detail. The optimal operation of user, regional, and cross-regional IES are taken as typical research objects and the research status of optimization problems and operation modes, energy management planning, and power market allocation are summarized and analyzed. Finally, the key scientific issues and related frontier technologies in the IES are concluded, and the future research directions are prospected.